P.R. Subramanian (Chief Editor). Tarkalat Tamil Maraputtotar Akarati (Tamil-Tamil-Ankilam) (Dictionary of Idioms and Phrases in Contemporary Tamil (Tamil-Tamil-English) - Murugan, G. (Lexikos, 1999)
Review of P.R. Subramanian (Chief Editor). Tarkalat Tamil Maraputtotar Akarati (Tamil-Tamil-Ankilam) (Dictionary of Idioms and Phrases in Contemporary Tamil (Tamil-Tamil-English)